Using a core word to identify different forms of semantically related formulaic sequences and their potential as a marker of authorship. Issue 3 (November 2016) - Larner, Samuel
Abstract : Formulaic sequences should make an excellent marker of style because if authors treat them as one lexical choice, they are unlikely to be aware of the individual words contained within. However, there is no clear-cut way to robustly identify all, and only, formulaic sequences in a text. If one particular word which occurs frequently in formulaic sequences – a core word – can be isolated, then a reasonable sub-set of word sequences will be identified, the majority of which can be expected to be formulaic. Using the core word way which occurs in many formulaic sequences (e.g., 'in a way', 'by the way' and 'by way of'), the aim of this research is to establish whether individual authors use different way- phrases from one another and, for comparative purposes, whether authors use alternative non-formulaic realisations of the same semantic content. If inter-authorial differences can be found, way -phrases may hold potential as a marker of authorship. The results indicate that for one author, the phrase 'in a way' appeared to be used distinctively. Therefore, there is potential for formulaic sequences to be used as a marker of authorship, albeit for only one author out of twenty, which limits the usefulness of such a marker in a forensic context.